Fault Diagnostic Methodology for Grid-Connected Photovoltaic Systems - Proenza Y. Roger; Camejo C. José Emilio; Ramos H. Rubén (Newinera Publisher, 2021)
This research focuses on the design of a fault diagnosis methodology to contribute to the improvement of efficiency, maintainability and availability indicators of Grid-Connected Photovoltaic Systems. To achieve this, we start from the study of the mathematical model of the photovoltaic generator, then, a procedure is performed to quantify the operational losses of the photovoltaic generator and adjust the mathematical model of this to the real conditions of the system, through a polynomial adjustment. A real system of nominal power 7.5 kWp installed in the Solar Energy Research Center of the province of Santiago de Cuba is used to evaluate the proposed methodology. Based on the results obtained, the proposed approach is validated to demonstrate that it successfully supervises the system. The methodology was able to detect and identify 100% of the simulated failures and the tests carried out had a maximum false alarm rate of 0.22%, evidencing its capacity.